Pneumocystis jirovecii Genotype Associated with Increased Death Rate of HIV-infected Patients with Pneumonia - Meja Rabodonirina; Laetitia Vaillant; Patrick Taffé; Aimable Nahimana; René-Pierre Gillibert; Philippe Vanhems; Philippe M. Hauser (Emerging Infectious Diseases, 2013)
Pneumocystis jirovecii dihydropteroate synthase (DHPS) mutations have been associated with failure of sulfa prophylaxis; their effect on the outcome of patients with P. jirovecii pneumonia (PCP) remains controversial. P. jirovecii DHPS polymorphisms and genotypes were identified in 112 cases of PCP in 110 HIV-infected patients by using PCR single-strand conformation polymorphism. Of the 110 patients observed, 21 died; 18 of those deaths were attributed to PCP. Thirty-three percent of the PCP cases involved a P. jirovecii strain that had 1 or both DHPS mutations. The presence or absence of DHPS mutations had no effect on the PCP mortality rate within 1 month, whereas P.jirovecii type 7 and mechanical ventilation at PCP diagnosis were associated with an increased risk of death caused by PCP. Mechanical ventilation at PCP diagnosis was also associated with an increased risk of sulfa treatment failure at 5 days.